PENGARUH KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA DAN KINERJA PEGAWAI PADA KANTOR BADAN PERTANAHAN NASIONAL KABUPATEN SITUBONDO - Lusiana Tulhusnah; Raden Andi Sularso; Muhammad Fathorrazi (Growth, 2018)
The research estimates the influence of Leadership and work Motivation on work Satisfaction and The Employees Performance.The research was done to some employees of National Land Agency office in Situbondo regency as many as 52 sample of people who were chosen as the respondence with various and different background of study, marriage status, sex, age and class position. A way of withdrawal sample is by the use of stratified random sampling, while the sheer size of the sample determined by using formula of Slovin. The kind of Thesis research is explanatory research.The measuring scale using likert scale by the span value 1 up to 5. The analysis instrument used in this research is Path Analysis, in which draft problem aims to know the influence of leadership against work satisfaction, motivation against work satisfaction, leadership against work dedication, motivation against dedication and work satisfactory against work dedication. From the analysis of the work of reliability and validity, had been done that all of questioner items represented by the variable are reliable and valid for the next analysis.The analysis result had been experienced that all the hypothesis were positive and significant. The result of the research reveal the influence of leadership style on work satisfaction of the employee. This discuss direct influence of the motivation on the employee’s work satisfaction, a direct impact of leadership style on employee’s performance and a direct impact of work satisfaction on employee’s performance in this research implies that it is important and necessary to consider the leadership style and work motivation in strategic planning to improve work satisfaction and employee’s performance of National Land Agency Situbondo District.